Nóvumok a megelőző polgári perjogunkhoz képest - Timár Balázs (2017)
The history of the Hungarian civil procedural law started more than a century ago. Since the very first code, Hungary had two codes in two different political, economic and social sphere. The last code entered power on 1st January 2018. However the new Civil Procedural Code seems to be an homage to the Hungarian legislation of the 20th century’s early decades, the similarity stops by the words themselves, their meaning is different. At the level of words, it was intended to return to Sándor Plósz's legacy, based on a modern, 21st century. It is mournful that the once coherent system has been dismantled and the legislative forces ignored the evolution of the decades of law in the past decades, blended with foreign solutions that resulted in a Hungarian law creating some sort of a hybrid law that was barely linked to its history. It can be stated that the undisputed advantage of the legislature of the 1950s was that there were specialists who were themselves active creators of the Soviet-era world of organization or they were acting as direct disciples. Accordingly, they possessed all that, according to the spirit of the age, were aligned with the laws of the age that had not been up to date. think about law. This article focuses on four areas. After discussing the need for the new regulation, it discusses the basic principles, then it turns to the certain changes in the judicial system, and concludes with the discussion of the civilian members. The three mentioned parts of the new code shows us where the legislation turned out to be committed for changes and where were ignorant to recreate not just the words but their meaning as well.
Keywords: Társadalomtudományok; Jogtudomány